2013
DOI: 10.1371/journal.pgen.1003420
|View full text |Cite
|
Sign up to set email alerts
|

Coincident Resection at Both Ends of Random, γ–Induced Double-Strand Breaks Requires MRX (MRN), Sae2 (Ctp1), and Mre11-Nuclease

Abstract: Resection is an early step in homology-directed recombinational repair (HDRR) of DNA double-strand breaks (DSBs). Resection enables strand invasion as well as reannealing following DNA synthesis across a DSB to assure efficient HDRR. While resection of only one end could result in genome instability, it has not been feasible to address events at both ends of a DSB, or to distinguish 1- versus 2-end resections at random, radiation-induced “dirty” DSBs or even enzyme-induced “clean” DSBs. Previously, we quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 52 publications
(109 reference statements)
6
49
1
Order By: Relevance
“…Blocked DNA ends occur in meiosis or during abortive topoisomerase reactions Longhese et al 2009). The MRN(X) complex and Sae2/CtIP may indeed be dispensable for the resection of "clean" DNA ends, as shown for HO-endonuclease and I-SceI-induced DSBs in yeast (Llorente and Symington 2004;Westmoreland and Resnick 2013). In contrast to a model, in which MRN(X) and Sae2/CtIP start resection directly at a DNA end, newer studies provide an alternative model, in which MRN(X) incises DNA away from the DNA end (Fig.…”
Section: Initiation Of Resection In Eukaryotesmentioning
confidence: 99%
“…Blocked DNA ends occur in meiosis or during abortive topoisomerase reactions Longhese et al 2009). The MRN(X) complex and Sae2/CtIP may indeed be dispensable for the resection of "clean" DNA ends, as shown for HO-endonuclease and I-SceI-induced DSBs in yeast (Llorente and Symington 2004;Westmoreland and Resnick 2013). In contrast to a model, in which MRN(X) and Sae2/CtIP start resection directly at a DNA end, newer studies provide an alternative model, in which MRN(X) incises DNA away from the DNA end (Fig.…”
Section: Initiation Of Resection In Eukaryotesmentioning
confidence: 99%
“…Unlike S1 nuclease, which also acts on ssDNA nicks (26,27), MBN is specific to ssDNA tails and gaps. Previously, we had addressed resection at random DSBs and found that duplex DNA with resected ssDNA tails of a few hundred to thousands of bases also exhibited retarded mobility on PFGE (referred to as "PFGE-shift") with a maximum apparent increase in molecular weight of 150 kb (18,28). However, there was no evidence of SMD or trapping of DNA in the well.…”
Section: Tls Deficiency Leads To Accumulation Of Ssdna Gaps and Reducedmentioning
confidence: 99%
“…NotI restriction enzyme treatments of sample plugs in Supplementary Figs. S4E and S4F were described in [10]. All PFGE separations were performed with a CHEF Mapper XA system (Bio-Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…For the PFGE conditions used in this study, short resection tracks of ~200 bases or less are barely detectable [9], but increasing the length of single-stranded ends up to ~3 kb progressively increases the mobility shift to a maximum apparent increase in chromosome size of about 40 kb (for 1-end resections) and about 140 kb (for 2-end resections). Extensive resection lengths greater than ~3 kb do not cause further increase in the apparent size of resected chromosomes [8,10]. Importantly, this difference between the maximum PFGE-shift for 1-end vs 2-end resections enables the assay to distinguish between 1-end and 2-end extensive resection events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation